THE SHIFT AND CONTINUITY OF THE PHILIPPINES’ FOREIGN POLICY UNDER RODRIGO DUTERTE ON THE SOUTH CHINA SEA ISSUE - Jennie Joyce Candice; Anak Agung Banyu Perwita (Universitas Jenderal Ahmad Yani, 2021)
The South China Sea (SCS) has become the largest and the crucial Sea Lanes of Communication (SLOCs) not only for Southeast Asia but also for the world. As one of the claimants of the South China Sea, Philippines were always and will always be trying to protect its national interests in the disputed waterways as part of its national territory. This article discusses about the shift and continuity of the Philippines’ foreign policy on the South China Sea issue. It explicates the shift and continuity of Philippines foreign policy under Rodrigo Duterte to the South China Sea. A more focus elaboration will be devoted on how the Philippines implemented its foreign policy to deal with China in the South China Sea dispute.It argues that Duterte foreign policy to this delicate issue is always based on the strategic dynamic of its “two-level game” (domestic and international political stimuli) to its national interests.